Ostracon, schrijftafel of boekrol? Jeremia 36, Jesaja 30:8 en twee ostraca uit Saqqara - Smelik, Klaas A. D. (Nederlands theologisch tijdschrift, 1990)
In this article the question is raised: How were the prophecies now to be found in the Prophetical Books of the Old Testament written down originally and what writing-material was used then? The author draws the attention to two Greek ostraca found near the Sacred Animal Necropolis at North Saqqâra. On these ostraca an Egyptian priest has written down five different versions of a letter containing a prophecy. The texts are translated and their implications for the earlier raised question are discussed.